THE INFLUENCE OF STRESS LEVELS ON ACNE VULGARIS IN STUDENTS OF STATE ISLAMIC UNIVERSITY NORTH SUMATERA MEDAN - Panggabean, Hikmah Tin; Fatima, Fatima; Tanjung, Putri Keza Hidayah; Ritonga, Sela; Wahyudi, Wahyudi (HEARTY, 2025)
Acne vulgaris is one of the skin problems often experienced by teenagers and young adults, including students, and can be triggered by various factors, one of which is stress. This study aims to determine the effect of stress levels on the occurrence of acne vulgaris among students at the State Islamic University North Sumatera Utara. The research uses a quantitative approach with a case-control design. Data were collected from 91 respondents through the DASS-42 questionnaire and direct observation of skin conditions. The results show that the majority of respondents were female (67.0%) and male (33.0%). As many as 92.3% of respondents experienced stress, and of that number, 64.8% experienced acne vulgaris. The Chi-Square test shows a significant relationship between stress levels and the occurrence of acne vulgaris (p = 0.037), with an odds ratio of 5.900. This means that students who experience stress have a 5.9 times greater risk of developing acne vulgaris compared to those who do not experience stress. The conclusion of this study is that stress has a significant impact on the occurrence of acne vulgaris, making stress management important in preventing this skin disorder among students.